Conductive Co-triazole metal-organic framework exploited as an oxygen evolution electrocatalyst. Issue 51 (9th June 2022) - Adpakpang, Kanyaporn; Pukdeejorhor, Ladawan; Ngamwongwan, Lappawat; Suthirakun, Suwit; Impeng, Sarawoot; Wannapaiboon, Suttipong; Chakthranont, Pongkarn; Faungnawakij, Kajornsak; Bureekaew, Sareeya
Abstract : Co-triazole MOF achieved via a facile microwave synthesis providing abundant catalytic sites and intrinsic electrical conductivity can efficiently catalyze the reaction at a low overpotential with fast kinetics towards the oxygen evolution reaction. Abstract : A Co-triazole metal-organic framework (Co-trz) endowed with electrical conductivity was synthesized effortlessly via a microwave-based method. Providing a high density of catalytic centers with electrically conductive features, as suggested by DFT calculations, the framework exhibited a low overpotential for the oxygen evolution reaction (OER) with good kinetics. A mechanistic reaction pathway was proposed based on monitoring alterations in the oxidation state and local coordination environment of Co centers upon the occurrence of the OER. Due to its performance and its chemical and electrochemical robustness, the framework was highlighted as a promising MOF electrocatalyst for the OER.